Tanggung Jawab Hukum Pelaku Usaha Terhadap Konsumen Dalam Perjanjian Jual Beli Properti di Indonesia - Rava Syhafa Maharani; Amad Sudiro (LPPM Universitas Ekasakti Padang, 2024)
The purpose of this research is to describe the form of legal liability that can be carried out by real estate companies that experience bankruptcy against consumers who are harmed by them. The method used in this research is normative juridical because the author seeks to conduct a critical analysis related to legal protection to consumers who are bound in a sale and purchase agreement with a real estate company. The rise of real estate companies experiencing bankruptcy due to the impact of the COVID-19 event has caused a situation that is detrimental to consumers of the real estate industry. The results of this study show that the bankruptcy condition experienced by PT Cowell has harmed consumers who are in the weakest position in the compensation repayment mechanism. Consumers as concurrent creditors are the last party to receive compensation after separatist creditors and preferred creditors have received compensation. Even though it has gone bankrupt, PT Cowell is still responsible for providing compensation to its consumers in accordance with the written agreement that was previously agreed upon and approved. The author considers that in order to protect consumers who have been harmed, government officials must act firmly against companies that cannot carry out their responsibilities properly.